Digital certificates : applied internet security - Feghhi, Jalal; Feghhi, Jalil; Williams, Peter (Addison-Wesley, 1999)
Detailed & practical guide to understanding & working with digital certificates. Presents an overview of this important technology & its role in Internet security, and looks at the business infrastructure that is essential to its effective utilization. CD ROM included.
Keywords: Computer Communication Networks; počítačové komunikační sítě; lékařská informatika